Pharmaceutical services and health promotion: how far have we gone and how are we faring? Scientific output in pharmaceutical studies - Carina Akemi Nakamura; Luciano Soares; Mareni Rocha Farias; Silvana Nair Leite (Universidade de São Paulo, 2014)
The objective of this study was to investigate the scientific output on health promotion within the pharmaceutical field and its relation with the development of pharmaceutical services within health systems. A comprehensive review of published scientific articles from the Medline and Lilacs databases was carried out. The review comprised articles published until December 2011, and used combinations of the terms 'health promotion' or 'health education' and 'pharmacy', 'pharmacist' or 'pharmaceutical'. The articles were selected according to inclusion and exclusion criteria. A total of 170 full texts and 87 indexed abstracts were analyzed, evidencing that most described actions of health promotion in community pharmacies and other services. Following the Ottawa Charter, most of the studies dealt with new guidance of the service and the supply of pharmaceutical information and services. It was concluded that there is a lack of theoretical background on health promotion in the pharmaceutical field to sustain the professional education and practice required by the health system and the population.